Проблема конкуренції латиниці й кирилиці в українській лінгвокультурі - Yelyzaveta Peresada (Acta Universitatis Wratislaviensis. Slavica Wratislaviensia)
The rivalry between two graphic systems, the Cyrillic alphabet and the Ukrainian Latin alphabet, can be traced throughout the history of the functioning of the Ukrainian language. During the 19th–21st centuries, Ukrainian linguists were continuosly analyzing the question issue of rivalry between Cyrillic and Latin alphabets in the Ukrainian linguoculture. The problem of the functioning of the Ukrainian Latin alphabet in the modern Ukrainian linguistic space during the globalization of English has been reemerged and continues to stir up the scientists. It expands the problematics of Ukrainian linguographic theory and reorients it toward a goal of the de-specifying information on this subject in the both diachronic and synchronic aspects of diachrony and synchrony.